A168 IS ROUTINE SCREENING FOR HEREDITARY COLORECTAL CANCER FEASIBLE IN AN OUTPATIENT GASTROENTEROLOGY PRACTICE?. (26th February 2020) - Smith, B C; Yonge, J; Macdonnell, C A; Poon, J; Galorport, C; Gillies, A; Chow, R; Enns, R A; Telford, J J
Abstract: Background: Lynch syndrome (LS) is the most common cause of hereditary colorectal cancer (CRC), with a reported prevalence of 2–5% of all CRC cases. A study by Kastrinos et al. found that a simple 3 item survey identified 77% of individuals at high risk for hereditary CRC. Implementation of this questionnaire at a gastroenterology office may help identify patients at risk for LS and other hereditary CRC. Aims: To assess whether implementation of a validated questionnaire to screen for hereditary CRC is feasible in an outpatient gastroenterology clinic. Methods: Adult gastroenterology outpatients who consented to participate in the study completed the screening questionnaire. Those who had previously been assessed by the Hereditary Cancer Program were excluded. Each subject was asked the following three questions: (1) Do you have a first-degree relative with CRC or LS-related cancer diagnosed before age 50? (2) Have you had CRC or polyps diagnosed before age 50? (3) Do you have ≥3 relatives with CRC?. Answering yes to any question was considered a positive screen. Results: A total of 288 patients were screened, with 12 (4.2%) screening positive for question 1, 28 (9.7%) screening positive for question 2, and 8 (2.8%) screening positive for question 3. In total, 14.2% of individuals surveyed screened positive. Conclusions: Utilization of a simple 3-question survey as part of regular patient intake in a gastroenterology office resulted in 14.2% of individuals screening high-risk for hereditary CRC. This is similar to the 15% screen positive rate in the original study of individuals with CRC. Further research is needed to determine whether a physician's knowledge of the questionnaire results will change management and whether a positive screen leads to a confirmed diagnosis of LS and other hereditary colorectal cancers. Funding Agencies: None